Shale Gas: An Indian Market Perspective - Paul, Dipen; Malik, Sushant; Mishra, Dharmesh K.; Hiwale, Rushik (International Journal of Energy Economics and Policy, 2020)
Energy demand has been increasing day by day with the advancement in industrialization and urbanization all across the world. Most of the demand is fulfilled with the help of primary conventional energy sources viz. coal and oil. One such source of energy is the shale from which oil and gas are extracted to be used as fuel. Shale gas resource has been visible on the global energy scenario map since the 1950s but was not being significantly focussed upon until 1990s when it gained economic and technical accessibility. The fast-technological breakthrough in the US resulted in fall in the breakeven cost of shale gas which had brought about a revolution in the US energy market in the 2000s. This revolution helped the US to turn itself from an importer of gas to an exporter of gas. Thus, it is important to discuss the current shale gas scenario, its prospects as well as its scope for growth in the future Indian energy market. Thus, the country needs to focus on the development of shale oil and shale gas resources as they have the potential to significantly contribute to the gas supply at a relatively low cost. Keywords: Shale gas, Indian shale, American Shale Revolution, Hydraulic fracturing, Horizontal drilling, Shale gas policy JEL Classifications: O3, O4 DOI: https://doi.org/10.32479/ijeep.10471